Berberine: A potential adjunct for the treatment of gastrointestinal cancers?. Issue 12 (20th August 2018) - Hesari, AmirReza; Ghasemi, Faezeh; Cicero, Arrigo F. G.; Mohajeri, Mohammad; Rezaei, Omid; Hayat, Seyed Mohammad Gheibi; Sahebkar, Amirhossein
Abstract: Gastrointestinal cancers are among the most prevalent cancers in the general population. Despite effective early diagnostics and intervention, the gastrointestinal cancer‐related mortality still remains elevated. Berberine (BBR) is a benzyl tetra isoquinoline alkaloid exracted from several plants. BBR is nontoxic to human normal cells, but suppresses the growth of different tumor cells: melanoma, epidermoid carcinoma, hepatoma, oral carcinoma, glioblastoma, prostatic carcinoma, and gastric carcinoma. In particular, BBR seems to suppress the proliferation of gastrointestinal cancers in a number of preclinical models. Several mechanisms of action have been hypothesized and demonstrated: immunomodulation, inhibition of topoisomerase enzymes, suppression of the EGF receptor, Her2/neu, and the VEGF receptor, induction of p53, Cip1/p21, Kip1/p27, Rb expression, induction of apoptosis (by regulation of MMPs pathway, caspases, Bax, and Smac/DIABLO), inhibition of arylamin N ‐acetyltransferase activity, and regulation of microRNAs expression. The aim of this review is to summarize the pharmacological effects of BBR on animal and human gastrointestinal cancers. Abstract : This review highlights the potential therapeutic role of berberine in gastrointestinal cancers. We have reviewed the molecular mechanisms of action of this alkaloid and the cellular targets through which berberine might exert its beneficial anti‐tumor effects.